History of development of the life-saving drug “Nusinersen” in spinal muscular atrophy - Qiu, Jiaying; Wu, Liucheng; Qu, Ruobing; Jiang, Tao; Bai, Jialin; Sheng, Lei; Feng, Pengchao; Sun, Junjie (Frontiers in Cellular Neuroscience, 2022)
Spinal muscular atrophy (SMA) is an autosomal recessive disorder with an incidence of 1/6,000–1/10,000 and is the leading fatal disease among infants. Previously, there was no effective treatment for SMA. The first effective drug, nusinersen, was approved by the US FDA in December 2016, providing hope to SMA patients worldwide. The drug was introduced in the European Union in 2017 and China in 2019 and has so far saved the lives of several patients in most parts of the world. Nusinersen are fixed sequence antisense oligonucleotides with special chemical modifications. The development of nusinersen progressed through major scientific discoveries in medicine, genetics, biology, and other disciplines, wherein several scientists have made substantial contributions. In this paper, we will briefly describe the pathogenesis and therapeutic strategies of SMA, summarize the timeline of important scientific findings during the development of nusinersen in a detailed, scientific, and objective manner, and finally discuss the implications of the development of nusinersen for SMA research.